Total Factor Energy Efficiency of Yangtze River Delta Region in China - Jiuwen Sun; Shanshan Li (European Regional Science Association (ERSA), 2014)
Energy is always the important material for economic growth and social development. A new index of energy efficiency called total factor energy efficiency (TFEE) consists of energy, capital, labor and other input that produce GDP as output. TFEE index is accounted by DEA through multiple input-output frameworks. Malmquist index measures productivity changing in two periods. Then decomposed the Malmquist index into efficiency change (EFFCH) and technical change (TECH) to estimate whether EFFCH or TECH influence TFEE. This paper analyze the energy consumption of two provinces and one city in Yangtze River Delta region, in terms of the quality of energy consumption and intensity of energy consumption. It shows that the increasing rate of energy consumption in the Yangtze River Delta was slowing down by using the absolute quantity of energy consumed in the region and its proportion in the country. Then the total factor energy efficiency of the Yangtze River Delta region was estimated by using the Yangtze River Delta region's energy consumption and economic growth data during from 1992 to 2010, based on DEA-Malmquist. The changes of total factor energy efficiency can be decomposed in energy efficiency and find the energy efficiency trends. The empirical results show that the Yangtze River Delta region, due to technological progress and technical efficiency, pulls together all the elements of energy efficiency. With time as a dimension, from 1992 to 2008, the TFEE is greater than 1, which means that the TFP is increasing and reaches the efficient frontier in the Yangtze River Delta Region. In a deeper analysis, the trend of total factor energy efficiency shows a W pattern, with the high point appearing in 1998 and 2007 by 5.4% and 5.2% respectively. And the main cause is the technical progress. With region as a dimension, from 1992 to 2008, the TFEE of the provinces and one city in the Yangtze River Delta Region are greater than 1. It indicates that the TFE climbs and reaches the efficient frontier. However, in Shanghai the TFEE is 1.060 which is the highest, followed by Jiangsu and Zhejiang.
Keywords: 330; Energy consumption; Economic growth; Energy efficiency; DEA-Malmquist